(untitled) (Papeles, 2024)
Introduction: Studies that address the diversity of learning styles, self-efficacy, and academic procrastination to deepen their relationship in favor of better school achievement have intensified, therefore the question to be answered in this study is what are the perspectives of High School students with different learning styles on self-efficacy and academic procrastination? To respond, the objective of the research was to identify the perspectives of senior high school students, with different learning styles, on self-efficacy and academic procrastination. Methodology: A qualitative method of interpretive paradigm with a hermeneutic approach was followed in which nine students (3 women, 6 men) from a public high school in the city of Puebla, Mexico voluntarily participated; with average age of 16.6 years. The Quirón Test questionnaire and the semi-structured interview were used to obtain information. Results and discussion: The participations showed that the establishment of goals in learning styles, subjects and assigned tasks influence their self-efficacy and procrastination. The lack of management of materials, activities and distractions causes, to a large extent, the procrastination of schoolwork. Conclusions: It is suggested to promote innovative pedagogical strategies in school environments to address the different learning styles of students to achieve greater self-efficacy and less academic procrastination.